Knee Fellowships Improve Clinical Practice and Scientific Activity - Riccardo D’Ambrosi, M.D.; Andy Williams, M.B., B.S., F.R.C.S. (Orth.).; Bertrand Sonnery-Cottet, M.D., Ph.D.; Christian Fink, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To determine the benefits of completing a knee fellowship for orthopaedic surgeons specializing in the treatment of sports injuries. Methods: An online survey was conducted to assess changes in clinical practice, and scientific activity in knee surgery, with special focus on the anterior cruciate ligament (ACL) before and after a knee fellowship. Results: A total of 74 of 102 (72.54%) fellows completed the survey. The mean age of the respondents was 36.85 ± 5.0 years (range 28-47 years). Sixty-nine (93.24%) were male, and 5 were female (6.75%). Before the fellowship, only 6 (8.10%) surgeons had performed more than 50 ACL surgeries yearly as the first operator, whereas more than 60% (46) had performed fewer than 10 ACL surgeries; after the fellowship, more than 50% (41) of the surgeons performed more than 50 ACL surgeries yearly as the first operator (P < .001). Before the fellowship, 57 (77.02%) surgeons did not perform anterolateral procedures or performed in less than 20% of their cases, whereas after the fellowship, almost 40% (31) performed anterolateral procedures in most of their cases (P < .001). A significant increase was also noted in the number of publications developed during the fellowship and conference presentations given between the period before and after the fellowship (P < .001). More than 90% (70%-94.59%) answered that they would do the fellowship again. Conclusions: Knee fellowships in highly specialized centers improve surgical activity in terms of surgical procedures and scientific production; furthermore, almost all the fellows reported that they would pursue such a fellowship again. Clinical Relevance: The results of this study may provide fellowship directors with important feedback about the strengths and weaknesses of the experience from participants.